Condom and Oral Contraceptive Use and Risk of Cervical Intraepithelial Neoplasia in Australian Women - Chih, Hui Jun; Lee, Andy; Colville, Linda; Xu, D.; Binns, Colin (Korean Society of Gynecologic Oncology, 2014)
Objective: To assess the association between condom use and oral contraceptive consumption and the risk of cervical intraepithelial neoplasia (CIN).Methods: A cross-sectional study was conducted in Perth clinics. A total of 348 women responded to the structured questionnaire. Information sought included demographic and lifestyle characteristics such as the use of condom for contraception, consumption of oral contraceptive, and duration of oral contraceptive usage. Crude and adjusted odds ratio (OR) and associated 95% confidence interval (CI) were calculated using unconditional logistic regression models and reported as estimates of the relative risk. Results: The prevalence of CIN was found to be 15.8%. The duration of oral contraceptive consumption among women with abnormal Papanicolaou (Pap) smear result indicating CIN was significantly shorter than those without abnormal Pap smear result (mean±SD, 5.6±5.2 years vs. 8.2±7.6 years; p=0.002). Comparing to =3 years usage, prolonged consumption of oral contraceptive for =10 years reduced the risk of CIN (p=0.012). However, use of condom for contraception might not be associated with a reduced risk of CIN after accounting for the effects of confounding factors (adjusted OR, 0.52; 95% CI, 0.05 to 5.11; p=0.577).Conclusion: Use of oral contraceptives, but not condoms, for contraception appeared to be inversely associated with CIN. Prolonged use of oral contraceptive demonstrated its benefits of reducing the risk of CIN.